An essay on the ethics of Islam towards environmental resources - Islam, Mohd Aminul (Kulliyyah of Science, IIUM, 2016)
In this paper, we have discussed the Islamic attitudes towards the environmental resources and the importance of its protection and preservation for sustaining life on earth. The paper maintains the view that the today’s outcry for environmental crisis is man-made. It is a consequence of humans’ irresponsible, irrational and thoughtless development activities for material gains. The environmental problem is so acute and widespread today that it becomes virtually impossible to get rid of. It is now a global concern. The paper stresses that a true believer who realizes and imbeds into his or her behavior or attitudes with the fundamental values of Islam such as- the concept of divine unity, trusteeship or amanah, justice and the responsibility as taught by the holy Qur’an and the prophetic traditions will be morally and spiritually uplifted which in turn will prepare him/her to use environmental resources rationally and responsibly. Rational and responsible use of environmental resources is a gesture of mans’ gratitude to Allah and His commands to ensure respects or honor towards the rights of other creatures which is essential to pave the way to maintain a state of balance in the environmental system. In other words, a true believer will abide by his/her creator to behave as a guardian of the earth, uphold His trust he/she is entrusted and behave not like a predator that can jeopardize the balance in the environment.